Experimental seismic behavior of a two-story CLT platform building. (15th March 2019) - van de Lindt, John W.; Furley, Jace; Amini, M. Omar; Pei, Shiling; Tamagnone, Gabriele; Barbosa, Andre R.; Rammer, Doug; Line, Philip; Fragiacomo, Massimo; Popovski, Marjan
Highlights: First shake table test of platform-style CLT construction with continuous hold down rods. Provides an opportunity assess stacked CLGT shear wall performance. Quantify the behavior of nailed angle connectors on CLT stacked shear wall dynamic performance. Assess the effect of transverse walls on CLT shear wall performance. Abstract: Cross-laminated timber (CLT) manufacturing and construction has been steadily growing since its inception in Europe in the 1990s. In the US, the growth of the CLT adoption is inhibited by the lack of codified design provisions for CLT in high seismic regions. This led to a multi-year study conducted by Colorado State University to investigate suitable seismic design parameters of CLT shear wall systems. This paper presents the results from a series of shake-table tests featuring a full-scale two-story mass-timber building utilizing CLT Seismic Force Resisting Systems (SFRS). The building was designed using an R- factor equal to 4.0 under the equivalent lateral force procedure specifications of the ASCE 7-16 Standard. The test program included three phases with different wall configurations, reflecting different wall panel aspect ratios and the existence of transverse CLT walls. Test results indicate that the code-level life safety objective was achieved in all test configurations. The addition of transverse walls did not affect the ability of the panels to rock, and improved the performance of the building structural system.